Pengembangan Media Pembelajaran Digital Sebagai Media Pembelajaran Pada Mata Pelajaran Administrasi Perpajakan di SMK Negeri 1 Tanjungpinang - Robby Krisyadi; Windy Sjachputri (ConCEPt - Conference on Community Engagement Project, 2021)
Starting from a local case, Covid-19 spread throughout the world one after another, including Indonesia. Since the beginning of 2020, the government issued a policy for teachers and students to carry out teaching and learning activities online while at their respective homes, as a form of prevention for the spread of the Covid-19 outbreak. With the existence of government policies, the learning system which is always implemented face-to-face has changed to have to go through digital media. However, the existence of weaknesses in this learning system can make students bored, less interested, and less interested in carrying out the learning process online. The activity began with an interview with the tax administration subject teacher about the difficulties in the teaching and learning process through digital media. The results of the interview, the authors found the problems faced by students of SMKN 1 Tanjungpinang, especially the Accounting Department, namely the difficulty of understanding the material being taught because they cannot interact directly. Therefore, SMKN 1 Tanjungpinang needs digital teaching materials on Tax Administration that are easy to understand by students at the school. The digital learning media produced from this activity is a module that is expected to help schools carry out teaching and learning activities with digital learning media and help and make it easier for students to understand and obtain alternative teaching materials besides books.